2017
DOI: 10.1111/ijsa.12168
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of unproctored internet testing and proctored paper‐and‐pencil testing of the Big Five

Abstract: The use of unproctored Internet‐based testing (IBT) for personality assessment is increasingly popular, especially in personnel selection. Previous studies on its equivalence to traditional proctored paper‐and‐pencil testing (PPT) have used between‐subjects designs, which makes it difficult to separate intergroup effects from format effects, and have shown mixed results. The aim of the present study was to assess the quantitative, qualitative, and auxiliary equivalence of unproctored IBT and proctored PPT of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
4
2
Order By: Relevance
“…In contrast, the present study found that all Big Five dimensions and their aspects were significantly correlated with g as well as with verbal and nonverbal intelligence. One possible explanation comes from the fact that correlations between personality scales in our sample were high ( Mdn r = .50), and significantly higher than previously reported for the LCPI in a sample of university students ( Mdn r = .23; Le Corff, Gingras, & Busque-Carrier, 2017). High stakes assessment settings such as personnel selection are known to produce more desirable personality profiles, that is, higher scores on Openness to Experience, Conscientiousness, Extraversion, Agreeableness, and Emotional Stability (Birkeland, Manson, Kisamore, Brannick, & Smith, 2006).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In contrast, the present study found that all Big Five dimensions and their aspects were significantly correlated with g as well as with verbal and nonverbal intelligence. One possible explanation comes from the fact that correlations between personality scales in our sample were high ( Mdn r = .50), and significantly higher than previously reported for the LCPI in a sample of university students ( Mdn r = .23; Le Corff, Gingras, & Busque-Carrier, 2017). High stakes assessment settings such as personnel selection are known to produce more desirable personality profiles, that is, higher scores on Openness to Experience, Conscientiousness, Extraversion, Agreeableness, and Emotional Stability (Birkeland, Manson, Kisamore, Brannick, & Smith, 2006).…”
Section: Discussioncontrasting
confidence: 63%
“…In contrast, the present study found that all Big Five dimensions and their aspects were significantly correlated with g as well as with verbal and nonverbal intelligence. One possible explanation comes from the fact that correlations between personality scales in our sample were high (Mdn r = .50), and significantly higher than previously reported for the LCPI in a sample of university students (Mdn r = .23; Le Corff, Gingras, & Busque-Carrier, 2017).…”
Section: Discussioncontrasting
confidence: 60%
“…These differences in data collection may impact results. However, studies suggest that paper-and-pencil and internet data collection are generally equivalent, and obtained data are comparable across formats (Le Corff et al., 2017; Weigold et al, 2013). We used computer-generated random responses and not simulations done by real participants (e.g., Dhillon et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Students have a positive attitude towards online proctoring when it does not affect their academic performance (Davis et al, 2016;Hollister & Berenson, 2009;Weiner & Hurtz, 2017). Le Corff and others reported when comparing five personality traits with an un-proctored online test and proctored paper test, the acceptance for both the method is equivalent (Le Corff et al, 2017). However, academic integrity should be maintained in both testing methods (Chuang et al, 2015;Medina & Castleberry, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%